EXPLORING DIGITAL GAME-BASED LEARNING FOR TEACHING POETRY IN MALAYSIAN PRIMARY ESL CLASSROOMS: A SYSTEMATIC REVIEW - Bolhan, Nur Syahadha; Ismail, Hanita Hanim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Poetry, though rich in linguistic and cultural value, poses notable challenges in ESL education due to its abstract themes, figurative language, and complex vocabulary. Digital Game-Based Learning (DGBL) has emerged as an innovative instructional approach to address these difficulties by making poetry lessons more interactive, engaging, and accessible for young learners. This systematic literature review aimed to examine the digital tools employed, the pedagogical benefits observed, and the implementation challenges associated with using DGBL to teach poetry to primary ESL students. A thorough search was conducted across databases including Google Scholar, ScienceDirect, and ERIC, focusing on studies published between 2019 and 2024. Out of 100 initially retrieved articles, 10 were rigorously selected for in-depth analysis following the PRISMA framework. Findings reveal that DGBL enhances student engagement, improves comprehension, increases motivation, cultivates positive learning attitudes, and supports language skill development through diverse, interactive poetic experiences. However, the review also highlights key challenges such as limited teacher familiarity with DGBL, a pressing need for targeted training, and varied student responses to game-based learning. These insights offer practical implications for educators and policymakers, emphasizing the need for effective DGBL integration and robust teacher professional development to support poetry learning in ESL contexts.